In vivo carbon-13 nuclear magnetic resonance studies of heart metabolism. - Neurohr, K J (Proc Natl Acad Sci U S A, 1983)
Guinea pig heart metabolism was studied in vivo by 13C NMR at 20.18 MHz. High-quality proton-decoupled 13C NMR spectra with excellent signal-to-noise ratios and resolution could be obtained in 6 min. Natural-abundance spectra showed resonances that could be assigned to fatty acids, but glycogen was not seen. During intravenous infusion of D-[1-13C]glucose and insulin, the time course of myocardial glycogen synthesis was followed serially for up to 4 hr. Anoxia resulted in degradation of the labeled glycogen within 6 min and appearance of 13C label in lactic acid. Infusion of sodium [2-13C]acetate resulted in incorporation of label into the C-4, C-2, and C-3 positions of glutamate and glutamine, reflecting "scrambling" of the label expected from tricarboxylic acid cycle activity. Examination of the 31P NMR spectrum of the guinea pig heart in vivo demonstrated no change in the high-energy phosphates during the time periods of the 13C NMR experiments. Our studies indicate that 13C NMR is a unique non-destructive tool for the study of heart metabolism in vivo.